2017
DOI: 10.1177/1049731517740958
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Focused Brief Therapy for Individuals With Alcohol Use Disorders in Chile

Abstract: This article presents a pilot study exploring the applicability of a linguistically adapted, solution-focused brief therapy (SFBT) program, implemented by social workers in Chilean primary care. Method: We completed a single-case design with eight replications. To analyze the results of the program on participants' alcohol use and other related variables, we conducted visual and percentage of nonoverlapping data analyses. Results: Social workers successfully implemented 10 of the 13 SFBT techniques. Although r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
4
0
1
Order By: Relevance
“…The mental health indicators in Chile prior to the outbreak indicated high levels of alcohol and substance abuse (González Suitt, Geraldo, Estay, & Franklin, 2019) as well as a high index of depressive disorders among adolescents and adults (Basso Musso, Mann, Strike, Brands, & Khenti, 2012; Toledo, Pizarro, & Castillo-Carniglia, 2015). In addition, Chileans’ mental health has been affected by aggravated socioeconomic and environmental conditions, such as natural disasters, significant social and economic inequalities, lack of trust in government institutions, and disparity in the access to health care and education (Rotarou & Sakellariou, 2017).…”
Section: How Do You Think the Pandemic Is Affecting The Population Fr...mentioning
confidence: 99%
“…The mental health indicators in Chile prior to the outbreak indicated high levels of alcohol and substance abuse (González Suitt, Geraldo, Estay, & Franklin, 2019) as well as a high index of depressive disorders among adolescents and adults (Basso Musso, Mann, Strike, Brands, & Khenti, 2012; Toledo, Pizarro, & Castillo-Carniglia, 2015). In addition, Chileans’ mental health has been affected by aggravated socioeconomic and environmental conditions, such as natural disasters, significant social and economic inequalities, lack of trust in government institutions, and disparity in the access to health care and education (Rotarou & Sakellariou, 2017).…”
Section: How Do You Think the Pandemic Is Affecting The Population Fr...mentioning
confidence: 99%
“…A recent cross-sectional study conducted in the United Kingdom found similar results, showing that greater financial hardship experienced during the pandemic was related to poorer mental health in adults ( Smith et al, 2020 ). This is particularly relevant for our national context in which studies prior to the COVID-19 pandemic showed a high frequency of depressive disorders ( Toledo et al, 2015 ) and substance abuse ( González Suitt et al, 2019 ), which were aggravated by socioeconomic inequalities ( Rotarou and Sakellariou, 2017 ).…”
Section: Discussionmentioning
confidence: 96%
“…Existing research on delity monitoring of SFBT interventions largely utilize the SFBT delity checklist, which relies on interventionist self-assessment 17 . The self-assessment scale has been utilized in research using SFBT among diverse populations including individuals with substance and alcohol use disorders [23][24][25] , children with Cerebral Palsy 26 , patients with HIV 27 , and children within the welfare system 28,29 , and how been found to be useful for acquiring a subjective interpretation of how intervention delity from the perspective of the interventionist. Though bene cial, utilizing clinician selfreport is limited as it relies on the subjective appraisal of the clinician to rate their adherence to the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Additional existing studies utilized methods of observation 25 , performing content analyses of recorded interviews 24 , and tracking the treatment outcomes 27 . Kim and colleagues also cite the use of a SFBT session manual form that was utilized by observers to analyze intervention integrity 25 .…”
Section: Discussionmentioning
confidence: 99%